An evaluation of 2-phase charge pump topologies with charge transfer switches for green mobile technology - Wong, Yan Chiew; Noordin, Nurul Hazlina; El-Rayis, Ahmed O.; Haridas, Nakul; Erdogan, Ahmet T.; Arslan, Tughrul S. (2011)
The development of charge pumps has been motivated by the power supply requirements of portable electronic devices. Charge pumps are inductorless DC-DC converters that are small size and high integration. The quality of the charge pump greatly depends on the effectiveness of switches to turn on and off at the designated clock phases. However, to date, no analysis has been carried out on the overall performance of charge pumps based on switch components in practice. This work demonstrates the characteristics of transistors as charge transfer switches and their effects on the performance of a charge pump. Three most common charge pump topologies are evaluated in terms of voltage drop due to on-resistance and charge loss per switch. Simulations are performed in 0.35μm Austriamicrosystems (AMS) technology for Dickson, Voltage Doubler and Makowski charge pump topologies in steady and dynamic states. In addition, the effect of switch parameters for different charge pump topologies are compared and analysed. We demonstrate that the Makowski charge pump is the topology for future green mobile technology.